Construction of nanostructures in aqueous solution from amphiphilic glucose‐derived polycarbonates. Issue 3 (19th September 2018) - Osumi, Shota; Felder, Simcha E.; Wang, Hai; Lin, Yen‐Nan; Dong, Mei; Wooley, Karen L.
ABSTRACT: Carbohydrates are the fundamental building blocks of many natural polymers, their wide bioavailability, high chemical functionality, and stereochemical diversity make them attractive starting materials for the development of new synthetic polymers. In this work, one such carbohydrate, d ‐glucopyranoside, was utilized to produce a hydrophobic five‐membered cyclic carbonate monomer to afford sugar‐based amphiphilic copolymers and block copolymers via organocatalyzed ring‐opening polymerizations with 4‐methylbenzyl alcohol and methoxy poly(ethylene glycol) as initiator and macroinitiator, respectively. To modulate the amphiphilicities of these polymers acidic benzylidene cleavage reactions were performed to deprotect the sugar repeat units and present hydrophilic hydroxyl side chain groups. Assembly of the polymers under aqueous conditions revealed interesting morphological differences, based on the polymer molar mass and repeat unit composition. The initial polymers, prior to the removal of the benzylidenes, underwent a morphological change from micelles to vesicles as the sugar block length was increased, causing a decrease in the hydrophilic–hydrophobic ratio. Deprotection of the sugar block increased the hydrophilicity and gave micellar morphologies. This tunable polymeric platform holds promise for the production of advanced materials for implementation in a diverse range of applications. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2019, 57, 432–440 Abstract : A series of glucose‐based amphiphilic polymers was synthesized via organocatalyzed ring‐opening polymerizations. The amphiphilic nature of these polymers was tuned using a post‐polymerization deprotection. The hydrophilic–hydrophobic ratio played an important role in the morphologies for this series of polymers and block polymers undergoing assembly in water, with low ratios producing vesicles and higher ratios producing micelles.